AD, Volume 12, n° 1, 1987 - Full Issue - journal system (Africa Development, 1987)
Table of Contents Race and Class Revisited: The Case of the North America and South Africa Bernard Magubane ........................ 5 Quelles Valeurs pour Quel Développement? Habib El Malki ......................... 43 Zone Franc, Sous-Développement et Dépendance en Afrique Noire Francophone Guy Martin ........................... 55 Land and Food Production in a Ghanaia Forest Community George J. S. Dei ........................ 101 Crise Alimentaire et Problématique du Développement Economique et Social en Afrique au Sud du Sahara François Bicaba ....................... 125 Political Access and Capital Accumulation: An Analysis of State Land Allocation Processess and Beneficiaries Peter Koehn ....................... 163 Publications Received ...................... 187 Index to Volume XI (1986) .................... 189